Perceived Ownership of Avatars Influences Visual Perspective Taking - Böffel, Christian; Müsseler, Jochen (Frontiers in Psychology, 2018)
Modern computer-based applications often require the user to interact with avatars. Depending on the task at hand, spatial dissociation between the orientations of the user and the avatars might arise. As a consequence, the user has to adopt the avatar's perspective and identify herself/himself with the avatar, possibly changing the user's self-representation in the process. The present study aims to identify the conditions that benefit this change of perspective with objective performance measures and subjective self-estimations by integrating the idea of avatar-ownership into the cognitive phenomenon of spatial compatibility. Two different instructions were used to manipulate a user's perceived ownership of an avatar used in otherwise identical situations. Users with the high-ownership instruction reported higher levels of perceived ownership of the avatar and showed larger spatial compatibility effects from the avatar's point of view in comparison to the low ownership instruction. This supports the hypothesis that perceived ownership benefits perspective taking.